PERWUJUDAN PRINSIP-PRINSIP KEPEMIMPINAN KEPALA DESA YANG DEMOKRATIS DALAM PENYELENGGARAAN PEMERINTAHAN DESA: DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Putra Astomo (Al-'Adl, 2018)
The village head is the most important actor in the administration of the Village Government. The figure of a village head in running a village government should show a democratic leadership attitude in order to create Good Governance in the village itself. UU no. 6 Year 2014 on the Village governing the authority of the village head in the administration of village administration. When it comes to principles of democratic leadership of course the village head has an obligation to behave democratically in the administration of village government based on the authorities it has.